1977
DOI: 10.1017/s0016756800036657
|View full text |Cite
|
Sign up to set email alerts
|

Scapolite compositional change in a metamorphic gradient and its bearing on the identification of meta-evaporite sequences

Abstract: Scapolite occurs in the NE Mt Lofty area of South Australia in rocks of bulk compositions as diverse as sulphide-rich veins, meta dolerite, scapolite (pelitic) schists, calc-silicate rocks and impure marbles. Scapolites analysed from all these rocks show with increasing grade a linear to near-linear change in composition from Me 50 and Me 66 . Some scatter around these values is attributed to local perturbations of falfco, in the fluid phase during metamorphism. Sulphur values as SO 3 are below the 0.02 level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The common occurrence of scapolite in the Northern Norrbotten Ore Province is suggested to reflect the occurrence of former evaporites within the stratigraphic record of the Kiruna Greenstones , in agreement with other studies suggesting that scapolite-rich metasedimentary units are commonly reflecting former evaporite-bearing strata (Ramsay and Davidson, 1970;Kwak, 1977;Ortega-Gutierrez, 1984). Strong, regional scapolite alteration, with no obvious relation to ores, is developed at two stratigraphic levels within the Kiruna Greenstones (Martinsson, 1997;2004a,b).…”
Section: Figure 19supporting
confidence: 86%
“…The common occurrence of scapolite in the Northern Norrbotten Ore Province is suggested to reflect the occurrence of former evaporites within the stratigraphic record of the Kiruna Greenstones , in agreement with other studies suggesting that scapolite-rich metasedimentary units are commonly reflecting former evaporite-bearing strata (Ramsay and Davidson, 1970;Kwak, 1977;Ortega-Gutierrez, 1984). Strong, regional scapolite alteration, with no obvious relation to ores, is developed at two stratigraphic levels within the Kiruna Greenstones (Martinsson, 1997;2004a,b).…”
Section: Figure 19supporting
confidence: 86%
“…These include metamorphism of evaporite-bearing sedimentary rock units (e.g., Rich, 1979;Mora and Valley, 1989;Oliver et al, 1992;Giuliani et al, 1995). Indeed, the presence of subordinate scapolite in marble interlayered with metapelite in the western metamorphic complex of the Muteh area is likely evidence of metaevaporites (Kwak, 1977;Moine et al, 1981;Faryad, 2002). A further possible source of saline fluids coexisting with CO 2 -rich fluids are magmatic intrusions (e.g., Nabelek and Ternes, 1997;Baker, 2002) emplaced at various stages during the evolution of the Sanandaj-Sirjan zone.…”
Section: Discussion Of the Fluid Inclusion Datamentioning
confidence: 99%
“…Therefore, a Cl-rich fluid is likely to have mobilised Zn, because the fluidrock fractionation factor is maximised by chlorocomplexes over other complexing ligands by virtue of their longer (and therefore weaker) bonds. The presence of saline fluids during metamorphism is also supported by Kwak (1977) and Hammerli et al (2013) who found evidence for circulation of a saline fluid with a major bittern brine component during metamorphism in the Kanmantoo Group. By contrast, we expect sulphur bearing species in the fluid had a trivial role in Zn or Pb transport, as S contents of all samples irrespective of metamorphic grades are consistently low (<50 μg g −1 ).…”
Section: Discussionmentioning
confidence: 66%